THE INTERACTION BETWEEN GENRES OF MAGIC SPELL AND NON-CANONICAL PRAYER (BASED ON CZECH MAGIC SPELLS) (Philological Studies, 2019)
Non-canonical prayers take up midline position between magic spells and canonical prayers, but technically they are closer to magic spells. This article devoted to analysis of intentional base, categories of addressee and addressant, situation and specific means of language in czech medical magic spells. It shows moments of interaction between genres of non-canonical prayer and magic spell. The aspect chosen for research helps us to answer the question about the difference of this genres.
Keywords: non-canonical prayer, magic spell, sacral texts, interaction between genres, verbal magic